Depression like-behavior and memory loss induced by methylglyoxal is associated with tryptophan depletion and oxidative stress: a new in vivo model of neurodegeneration - Md. Samsuzzaman; Seong-Min Hong; Jae Hyuk Lee; Hyunjun Park; Keun-A Chang; Hyun-Bum Kim; Myoung Gyu Park; Hyeyoon Eo; Myung Sook Oh; Sun Yeou Kim (Biological Research)
Abstract Background Depression and memory loss are prevalent neurodegenerative disorders, with diabetic patients facing an elevated risk of brain dysfunction. Methylglyoxal (MGO) formation, which is heightened in diabetes owing to hyperglycemia and gut dysbiosis, may serve as a critical link between diabetes and brain diseases. Despite the high prevalence of MGO, the precise mechanisms underlying MGO-induced depression and memory loss remain unclear. Results We investigated the effect of MGO stress on depression like-behavior and memory loss to elucidate the potential interplay between MGO-induced tryptophan (Trp) metabolism impairment and oxidative stress in the brain. It demonstrates that MGO induces depression-like behavior in mice, as confirmed by the OFT, TST, FST, SPT, and EPM behavioral tests. MGO led to the depletion of Trp and related neurotransmitters as 5-HT, EPI, and DA in the mouse brain. Additionally, MGO reduced the cell count in the DG, CA1, and CA3 hippocampal regions and modulated TPH2 levels in the brain. Notably, co-treatment with MGO and Trp mirrored the effects observed after Trp-null treatment in neurons, including reduced TPH1 and TPH2 levels and inhibition of neuronal outgrowth. Furthermore, MGO significantly altered the expression of key proteins associated with neurodegeneration, such as p-Tau, p-GSK-3β, APP, oAβ, BDNF, NGF, and p-TrkB. Concurrently, MGO activated MAPKs through ROS induction, triggering a redox imbalance by downregulating Nrf-2, Ho-1, TXNRD1, Trx, Sirt-3, and Sirt-5 expression levels, NAD+, and CAT activity in the mouse brain. This led to an accelerated neuroinflammatory response, as evidenced by increased expression of Iba-1, p-NF-κB, and the secretion of IL-6 and TNF-α. Importantly, Trp treatment ameliorated MGO-induced depression like-behavior and memory loss in mice and markedly mitigated increased expression of p-Tau, APP, p-ERK1/2, p-pJNK, and p-NF-κB in the brain. Likewise, Trp treatment also induced the expression of MGO detoxifying factors GLO-I and GLO-II and CAT activity, suggesting the induction of an antioxidant system and reduced inflammation by inhibiting IL-6 and TNF-α secretion. Conclusions Our data revealed that MGO-induced depression like-behavior and memory deficits resulted from disturbances in Trp, 5-HT, BDNF, and NGF levels, increased p-Tau and APP expression, neuroinflammation, and impaired redox status (Nrf-2/Ho-1/TXNRD1/Sirt3/5) in the brain.